The Non-synonymous rs763780 Single-Nucleotide Polymorphism in IL17F Gene Is Associated With Susceptibility to Tuberculosis and Advanced Disease Severity in Argentina - Rolandelli, Agustín; Pellegrini, Joaquín Miguel; Hernández Del Pino, Rodrigo Emanuel; Tateosian, Nancy Liliana; Amiano, Nicolás Oscar; Morelli, María Paula; Castello, Florencia Andrea; Casco, Nicolás; Levi, Alberto; Palmero, Domingo Juan; García, Verónica Edith (Frontiers in Immunology, 2019)
Th17 lymphocytes, that produce IL17A, IL17F, and IL22, play a crucial role during the immune response against Mycobacterium tuberculosis (Mtb) infection. Whereas, the contribution of IL17A in immunity to tuberculosis is usually accepted, the role of IL17F has been scarcely studied so far. The aim of this work was to evaluate the existence of a potential association of the non-synonymous variant rs763780 SNP of the IL17F gene with human tuberculosis. Accordingly, by comparing healthy donors (HD) and tuberculosis patients (TB) populations we demonstrated an association between the C allele of the SNP and the susceptibility to tuberculosis disease in Argentina. Furthermore, we found that peripheral blood mononuclear cells (PBMCs) from individuals with a more effective immune response against Mtb secreted the highest levels of IL17F when stimulated with a lysate of Mtb (Mtb-Ag). Besides, we evidenced that Mtb-Ag-stimulated PBMCs from HD carrying the C variant of the SNP displayed the lowest IFNG secretion, proliferation index, and SLAM expression as compared to TT carriers. Moreover, Mtb-Ag-stimulated PBMCs from TB carrying the C allele produced the lowest levels of IFNG, the highest level of IL17A, and the minimum proliferation indexes as compared to TT TB, suggesting a relationship between the C allele and tuberculosis severity. In fact, TB carrying the C allele presented a more severe disease, with the highest bacilli burden in sputum. Together, our findings identify the IL17F rs763780 SNP as a biomarker of tuberculosis susceptibility and advanced disease severity in Argentina, suggesting that IL17F could be a critical cytokine in tuberculosis immunity.